THE EMERGENCE OF THE CONCEPT OF AIR POWER ACCORDING TO THE TEACHINGS OF GIULIO DOUHET - Budimir, Zeljko (Politeia, 2025)
The revolutionary essence of the emergence of air power during the First World War led to the theoretical formulation of the concept of air power, where Italian general Giulio Douhet retains an exceptional standing. The theoretical concepts, that emerged in this early technological period of aviation development carried a more "prophetic" character of the future use of the combat aircraft, than a footing in practical service and warfare experience. The third dimension of power, reaching from the atmosphere presents a new dynamic and a revolutionary change to warfare erasing the distinction between front and rear. In his works, General Douhet’s forms a modern warfare theory and attacks the fundamental postulates of military thinking based on a conflict exclusively split into two dimensions: land or sea. Of distinct importance is his understanding of the significance of the moral factor in war, among soldiers and civilians. According to his learning, the moral factor carries the same or greater significance than the material destruction in war. According to this doctrine, the air force, and especially bomber aviation, has a strategic character and should independently make decisions regarding the outcome of the war itself. General Douhet ’s air (geo)strategy was supposed to transform the war, reduce heavy losses, and bring a swift ending to the armed conflict. Nonetheless, it was the Air Force itself responsible for the tremendous devastation of the cities and massive casualties of the civilian population during World War II, Cold War local conflicts, and today’s wars. The works of Giulio Douhet had a significant influence on other classical and contemporary air power theorists, but also on the main staffs of the great powers that determined the air doctrines of their armed forces.